2009
DOI: 10.1002/ptr.2992
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm phenylethanoid glycosides from Penstemon centranthifolius

Abstract: Bioassay-guided fractionation of the antibacterial ethyl acetate-ethanol (50 : 50) extract obtained from the aerial parts of Penstemon centranthifolius led to the isolation of six phenylethanoid glycosides (1-6) and eleven iridoid glycosides (7-17). Their structures were determined on the basis of spectroscopic analysis and comparison with the literature. Among them, two phenylethanoid glycosides, 4'''-O-acetylverbascoside (1) and verbascoside (2), were found to show significant inhibition of the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Fourth, while there are purported advantages of tumour palpation and intraoperative decision‐making on improved cancer control during open compared with minimally invasive radical prostatectomy [6], most US men with prostate cancer increasingly present with raised PSA levels and low‐volume disease rather than with disease that is palpable on digital rectal examinations [10,27], and our population‐based analyses show similar positive surgical margin rates between minimally invasive and open radical prostatectomy. Moreover, early cancer control was also similar for minimally invasive and open radical prostatectomy from a study of SEER‐Medicare linked data [7]. Our findings contrast with those contending that men undergoing minimally invasive vs open radical prostatectomy experience inferior cancer control [4,28].…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Fourth, while there are purported advantages of tumour palpation and intraoperative decision‐making on improved cancer control during open compared with minimally invasive radical prostatectomy [6], most US men with prostate cancer increasingly present with raised PSA levels and low‐volume disease rather than with disease that is palpable on digital rectal examinations [10,27], and our population‐based analyses show similar positive surgical margin rates between minimally invasive and open radical prostatectomy. Moreover, early cancer control was also similar for minimally invasive and open radical prostatectomy from a study of SEER‐Medicare linked data [7]. Our findings contrast with those contending that men undergoing minimally invasive vs open radical prostatectomy experience inferior cancer control [4,28].…”
Section: Discussionmentioning
confidence: 42%
“…We identified 6153 men aged ≥65 years enrolled in Medicare Parts A and B, not enrolled in the Medicare health maintenance organization (because their claims were not reliably submitted), diagnosed with prostate cancer in 2004 and 2005 who underwent open and minimally invasive radical prostatectomy from 2004 to 2006. We stratified the surgical approach on the basis of the Physicians Current Procedural Terminology Coding System 4th edition, (CPT‐4): 55840, 55842, 55845 for open retropubic radical prostatectomy; and 55866 for minimally invasive radical prostatectomy [4,7]. Because SEER only captures positive margin characteristics for the American Joint Commission on Cancer pathological T2 and T3a disease, we excluded 293 men with pathological stage T3b, 63 men with pathological T4 and 1132 men with missing pathological information.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, the activities of 121 (MIC = 2.1ˆ10´4 and 4.1ˆ10´4 M) and 125 (MIC = 3.4ˆ10´4 M) against SA 1199B (NorA) and XU 212 (TetK/MecA), respectively, were comparable to those of the positive control, norfloxacin (MIC = 1.0ˆ10´4 and 2.5ˆ10´5 M) [90]. In addition, 4 111 -O-acetylacteoside (133) and 121 possessed significant inhibition of the formation of bacterial biofilms by E. coli UTI89 [91]. The antifungal/antimicrobial effect of PhGs may be largely due to the presence of phenolic hydroxyls which have high affinity with proteins [92].…”
Section: Antibacterial and Antivirus Activitymentioning
confidence: 92%
“…Extracts and pure compounds of P. gentianoides and Penstemon campanulatus(Domínguez et al 2010(Domínguez et al , 2011, as well as Penstemon roseus (García-Rodríguez et al 2011), Penstemon barbatus and P. campanulatus (Moreno-Escobar et al 2011), have revealed anti-oxidant and cytotoxic activities. Moreover, some very interesting results have been published recently from several compounds (phenylethanoid glycosides as well as iridoid glycosides) isolated from Penstemon centranthifolius, showing significant inhibition of the formation of bacterial biofilms by Escherichia coli UTI89(Ye et al 2010).…”
mentioning
confidence: 99%